Human-Robot Interaction Using Open BCI Through Visual Simulation Using Python Programming - Anantha Kamal Nallamothu; Seshu Kishan Nallamothu (AG Volumes, 2022)
In order to improve the efficiency of robots that interact with humans in the real world, HRI (human robot interaction) researchers may choose to work as roboticists, designing cutting-edge robotic systems that might have real-world applications. Motivated by the aim of restoring independence to severely injured persons and by curiosity in further extending the human control of the external systems, researchers from many domains are participating in this hard new effort. BCI research & development have evolved explosively during the last two decades. "Brain-computer interfaces" (BCIs) enable its users to communicate as well as control the external devices using brain impulses rather than the brain’s regular output channels of peripheral nerves and muscles. In this study, we evaluate the present state and future possibilities of BCI technology plus investigate impending issues that are projected to have a substantial influence on the area.